PENERAPAN AKUNTANSI MANAJEMEN LINGKUNGAN TERHADAP LIMBAH PADA PABRIK GULA PRADJEKAN - Gunaawan, Eko; sugeng, Sugeng (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTThe impact of a company's production activities can cause various environmental problems that are detrimental to various parties. This is a social burden, which must be taken seriously. Environmental Management Accounting (EMA) is a concept that helps companies in loading business impacts in the form of monetary units. The application of Environmental Management Accounting helps companies with environmental problems by recording all of their production activities to be reported in the company's environmental cost report. This research is a case study research in manufacturing companies, namely PG.PRADJEKAN. This study aims to evaluate the application of Environmental Management Accounting PG.PRADJEKAN. From the results of research on PGADJEKAN, it is known that the company has not fully implemented Environmental Management Accounting. Especially for accountant staff who do not understand about Environmental Management Accounting should be given a study of Environmental Management Accounting. From the implementation of Environmental Management Accounting in 2011 until now the company has a good waste management system so as to minimize environmental pollution caused by production activities in the milling season. From the evaluation results in this study it can be seen that the company's accountants play a full role in the application of Environmental Management Accounting, but accountants need to conduct further environmental studies to understand their application, because the application of Environmental Management Accounting in PG.PRADJEKAN has only been running for four years.Keywords: Evaluation, Application of Environmental Management Accounting, Environmental Costs